2012
DOI: 10.2106/jbjs.k.00436
|View full text |Cite
|
Sign up to set email alerts
|

Single Versus Double-Incision Technique for the Repair of Acute Distal Biceps Tendon Ruptures

Abstract: There were no significant differences in outcomes between the single and double-incision distal biceps repair techniques other than a 10% advantage in final flexion strength with the latter. Most complications were minor, with a significantly greater prevalence in the single-incision group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
134
6
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 21 publications
5
134
6
5
Order By: Relevance
“…Single incision surgery also lent itself to the newly introduced interference screw and cortical button techniques. There is still great debate as to whether one or 2 incision techniques have an effect on the risk of neurological injury [10,12]. However, it is now widely reported that range of movement outcomes are equivalent whether undertaken by a modified Boyd-Anderson or a single anterior incision approach [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single incision surgery also lent itself to the newly introduced interference screw and cortical button techniques. There is still great debate as to whether one or 2 incision techniques have an effect on the risk of neurological injury [10,12]. However, it is now widely reported that range of movement outcomes are equivalent whether undertaken by a modified Boyd-Anderson or a single anterior incision approach [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is now widely reported that range of movement outcomes are equivalent whether undertaken by a modified Boyd-Anderson or a single anterior incision approach [17]. Grewal, et al [10] randomised control of the study, and in interpretation of the results. PG, MB & AM prepared data from follow up.…”
Section: Discussionmentioning
confidence: 99%
“…With great interest we have read the article of Grewal and colleagues [1] . We have however, some comments on this trial and think that the conclusions of this article should be interpreted in this light.…”
Section: To the Editormentioning
confidence: 99%
“…However, the best approach for repair (single vs double incision) is still subject of debate. Grewal et al [1] recently presented the results of the largest randomized clinical trial evaluating two different surgical approaches for the repair of distal biceps tendon ruptures. In this great piece of research were 91 acute distal biceps tendon ruptures randomized between a single incision repair with use of suture anchors (n = 47) or double incision repair with use of transosseous drill holes (n = 44).…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation